The Role of Religious Institutions in Confronting Violence, Extremism, and Terrorism: The Directorate of Endowments in Anbar as a Model - Al-Saadi, Prof. Dr. Muadh Abdel Aleem Abdul Rahman Al-Saadi; Al-Fahdawi, Asst. Prof. Dr. Taha Hameed Hareesh Al-Fahdawi (Sulaimani Journal for Humanities, 2026)
The dangers of violence, terrorism, and extremism at all levels are undeniable, due to their profound impact on both individuals and society—challenges that societies have suffered throughout history. Governments, states, and individuals have all risen to confront these challenges, recognizing early on the severity of extremist ideology. Consequently, they adopted preventive approaches employing various means, focusing on effective actions and diverse strategies to combat terrorism and violent extremism. It is clear that these phenomena cannot be eliminated or fought solely through repressive measures. Instead, there is a continued need for a comprehensive approach involving the entire society, aligned with human rights and sensitive to diverse considerations.Security upbringing cannot be achieved except through deepening dialogue and active openness among institutions to discuss the problems facing community members and to develop shared visions, plans, and strategies between institutions to confront and reduce these issues.
Keywords: Institution; Religion; Violence; Extremism; Terrorism